Intelligence services at the service of democratic society and constitutional order: Socio-legal reflections on legal intelligence, disinformation strategies, and lawfare - Cortés Villanueva, Daniel (Journal of the Spanish Institute for Strategic Studies, 2026)
This work presents a socio-legal analysis of intelligence services and their crucial role in defending democracy and constitutional order, in the context of a growing need to address new challenges and move beyond current classical models, due to the tension between the need for national security, the preservation of civil liberties, and fundamental rights.
Keywords: Intelligence services; Constitutional order; Disinformation; Lawfare